2017
DOI: 10.1210/en.2017-00565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to the Endocrine-Disrupting Chemical Bisphenol A During Critical Windows of Murine Pituitary Development

Abstract: Critical windows of development are often more sensitive to endocrine disruption. The murine pituitary gland has two critical windows of development: embryonic gland establishment and neonatal hormone cell expansion. During embryonic development, one environmentally ubiquitous endocrine-disrupting chemical, bisphenol A (BPA), has been shown to alter pituitary development by increasing proliferation and gonadotrope number in females but not males. However, the effects of exposure during the neonatal period have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…one in mice (van Esterik et al, 2014 [RefID 7393]) and six studies in rats (Jiang et al, 2014 [RefID 3190]; Lejonklou et al, 2017 [RefID 3975]; Xia et al, 2014 [RefID 8103]; NTP Clarity Report, 2018/Camacho et al, 2019 [RefID 11370]; Dunder et al, 2018 [RefID 11866]; Greenberg, 2018 (NTP Grantee study) [RefID 13785]); four Tier 2 studies, i.e. three in mice (Eckstrum et al, 2018 [RefID 11874]; Esplugas et al, 2018 [RefID 11900]; Meng et al, 2018a [RefID 12708]) and one in rats (Quan et al, 2017 [RefID 6025]); one Tier 3 study in rats (Sadowski et al, 2014a [RefID 6361]).…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…one in mice (van Esterik et al, 2014 [RefID 7393]) and six studies in rats (Jiang et al, 2014 [RefID 3190]; Lejonklou et al, 2017 [RefID 3975]; Xia et al, 2014 [RefID 8103]; NTP Clarity Report, 2018/Camacho et al, 2019 [RefID 11370]; Dunder et al, 2018 [RefID 11866]; Greenberg, 2018 (NTP Grantee study) [RefID 13785]); four Tier 2 studies, i.e. three in mice (Eckstrum et al, 2018 [RefID 11874]; Esplugas et al, 2018 [RefID 11900]; Meng et al, 2018a [RefID 12708]) and one in rats (Quan et al, 2017 [RefID 6025]); one Tier 3 study in rats (Sadowski et al, 2014a [RefID 6361]).…”
Section: Assessmentmentioning
confidence: 99%
“…No changes in liver weight were reported in three studies in mice up to doses of 3000 μg/kg bw per day (van Esterik et al, 2014 [RefID 7393]; Eckstrum et al, 2018 [RefID 11874]; Meng et al., 2018a [RefID 12708]) and in six studies in rats up to doses of 50,000 μg/kg bw per day (Jiang et al, 2014 [RefID 3190]; Lejonklou et al, 2017 [RefID 3975]; Sadowski et al, 2014a [RefID 6361]; Xia et al, 2014 [RefID 8103]; Dunder et al, 2018 [RefID 11866] and Greenberg ( 2018 ) (NTP Grantee study) [RefID 13785]). In one rat study, liver weight decreased in males (females not tested) at 1,000 and 100,000 μg/kg bw per day but without dose–response (Quan et al, 2016 [RefID 6024]) and there was a trend indicating an increase of liver weight in male rats treated with doses between 2.5 and 25,000 μg/kg bw per day but not in female rats (NTP Clarity Report, 2018/Camacho et al, 2019 [RefID 11370]).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, several authors reported that exposure of neonatal mice to BPA can disrupt pituitary development, with critical effects on their pubertal and hence gonadal development. The described effects comprise a measurable downregulation of the mRNA expression of several genes (including pomc and Icam5) involving different estrogen-related pathways, with sex-specific differences [68,69]. Furthermore, there is evidence from an animal study that the spectrum of reproductive alterations induced by chronic BPA exposure includes reproductive hormone alterations (increased gonadotropins and estradiol, reduced testosterone), spermatogenesis hindrance and increased oxidative stress [70].…”
Section: Postnatal Exposure: Are There Repercussions For Adult Testicmentioning
confidence: 99%
“…In contrast to this, irreversible organizational effects were produced in Sprague-Dawley rats after neonatal and perinatal exposure [11]. BPA at high and low doses causes long-term adverse reproductive and carcinogenic effects if exposure occurs during critical periods of differentiation, causing precocious hypothalamic-pituitary maturation and precocious puberty [12,13]. Prenatal exposure to BPA is associated with an increase in the risk for breast cancer [14].…”
Section: Introductionmentioning
confidence: 99%